70 ans de justice administrative de proximité (EPURE, Éditions et presses universitaires de Reims, 2026)
In 2023, the anniversary of the administrative courts – established by the decree of 30 September 1953 – provides a fitting opportunity to look back on seventy years of administrative case law. Academics, judges and lawyers analyse the development of a justice system that the 1953 reform had regionalised. Drawing on the most significant cases heard by the Administrative Court of Châlons-en-Champagne, and taking into account the specific characteristics of the territory within this court’s jurisdiction, these studies offer an original insight into the evolution of legal instruments and the relationship between the administrative judge, the litigant and the administration.